Analysis Of The Concept Of Re-Engineering In Gas Distribution Projects To Improve Project Implementation Efficiency - Elang Kuncoro Jati (CV. Publikasi Indonesia, 2026)
Gas distribution projects are part of energy infrastructure that require high efficiency in terms of time, cost, and quality of implementation. However, in practice, several main work items are still carried out using conventional methods that potentially lead to resource inefficiencies. This study aims to analyze the application of the re-engineering concept in the implementation methods of gas distribution projects to improve overall project efficiency. This research employs a mixed-methods approach, combining quantitative and qualitative analyses. The analysis focuses on two main work items, namely excavation works and polyethylene (PE) pipe installation. The existing method, open cut excavation, is compared with alternative methods resulting from the re-engineering process, namely the combination of open cut with manual horizontal boring and open cut with the Horizontal Directional Drilling (HDD) method. Quantitative data were obtained from the analysis of the cost budget plan, S-curve schedule, work duration, and labor productivity, while qualitative data were collected through field observations, interviews, and project document reviews. The results indicate that the application of the re-engineering concept to construction methods significantly improves project time and cost efficiency. Alternative methods using manual horizontal boring and HDD are proven to be more effective under certain conditions compared to the existing method, particularly in reducing work duration and indirect project costs. This study is expected to serve as a reference for PT PGAS Solution and other construction practitioners in selecting more efficient, economical, and sustainable gas distribution project implementation methods.